The Natural Product Magnolol as a Lead Structure for the Development of Potent Cannabinoid Receptor Agonists - Fuchs, Alexander (Public Library of Science, 2013)
Magnolol (4-allyl-2-(5-allyl-2-hydroxyphenyl)phenol), the main bioactive constituent of the medicinal plant Magnolia officinalis, and its main metabolite tetrahydromagnolol were recently found to activate cannabinoid (CB) receptors. We now investigated the structure-activity relationships of (tetrahydro)magnolol analogs with variations of the alkyl chains and the phenolic groups and could considerably improve potency. Among the most potent compounds were the dual CB(1)/CB(2) full agonist 2-(2-methoxy-5-propyl-phenyl)-4-hexylphenol (61a, K (i) CB(1)∶0.00957 µM; K (i) CB(2)∶0.0238 µM), and the CB(2)-selective partial agonist 2-(2-hydroxy-5-propylphenyl)-4-pentylphenol (60, K (i) CB(1)∶0.362 µM; K (i) CB(2)∶0.0371 µM), which showed high selectivity versus GPR18 and GPR55. Compound 61b, an isomer of 61a, was the most potent GPR55 antagonist with an IC(50) value of 3.25 µM but was non-selective. The relatively simple structures, which possess no stereocenters, are easily accessible in a four- to five-step synthetic procedure from common starting materials. The central reaction step is the well-elaborated Suzuki-Miyaura cross-coupling reaction, which is suitable for a combinatorial chemistry approach. The scaffold is versatile and may be fine-tuned to obtain a broad range of receptor affinities, selectivities and efficacies.